S1 table : mapping of the sites of Trypanosoma cruzi kDNA integration into the rabbits’ genome* - Teixeira, Antonio Raimundo Lima Cruz (2022)
* Oryctolagus cuniculus whole Genome (OryCun2.0 reference Annotation Release 102) shot gun sequence.